Determinants Aﬀecting the Adoption of Silvopastoral Production among Smallholder Farmers in Zimbabwe - Christopher Gadzirayi; Chimvuramahwe J; Nhundu A (Journal of Extension Education, 2023)
The main goals of silvopastoral production are to increase the quality and production of fodder and promote the conservation of soil and biodiversity. Despite its achievements as an approach, it has not been fully practiced by small holder farmers. The study sought to determine the factors inﬂuencing the adoption of silvopastoral production in Chikwaka communal area in Goromonzi district of Zimbabwe. Simple random sampling technique was used involving sixty-six respondents. Factors that aﬀect adoption were estimated by binary logistic regression model. Variables that signiﬁcantly aﬀected the adoption of silvopastoral were land size, number of cattle owned as well as household size. The results revealed that uptake level of silvopastoral is still low . Therefore, the continuous eﬀort to improve livestock herd under smallholder farmers through silvopastoral, should be taken as a priority to encourage more farmers to adopt the system.